Bereavement Support Services in a National Sample of Hospices: A Content Analysis. (March 2023) - Becker, Todd D.; Cagle, John G.
Although the Medicare Hospice Benefit mandates that hospices offer bereavement support services to families for at least 1 year following the death of a patient, it does not stipulate which services they should offer. As a result, little is known about what bereavement support services hospices provide, especially on a national scale. The current study recruited a national sample of hospice representatives who responded to an open-ended question that asked, "What types of bereavement support services does your hospice provide to families?" Seventy-six viable responses were recorded and content analyzed. Four overarching domains emerged: (a) timing of support, (b) providers of support, (c) targets of support, and (d) formats of support. Other notable findings included the underutilization of bereavement support services and the utility of informal support formats. These findings present implications for future study regarding which specific aspects of hospice bereavement support services are most beneficial to bereaved families.